Hubungan Penggunaan Gadget dengan Prestasi Belajar Siswa Kelas Tinggi SD Inpres yang 7/83 Manurunge Kecamatan Ulaweng Kabupaten Bone - Satriani DH; Asriadi; Arabe, Zahra Paraditat Sauri (MACCA : Science-Edu Journal, 2025)
This study is a quantitative study with a correlational type that aims to describe use of gadget and learning achievement of high students in high grades, as well as to find out the significant relationship use of gadget with learning achievement high grade students of SD Inpres 7/83 Manurunge Ulaweng Subdistrict Bone Regency. The samples used in this study were grade IV, V and VI students of SD Inpres 7/83 Manurunge totaling 21 students, with non probability sampling technique. Research data were obtained through questionnaires and documentation. Data analysis techniques using descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, it was obtained that the use of gadget were in the good category (76,73%). Meanwhile, students' learning achievement was in the good category with a percentage of 74,57%. The results of inferential statistical analysis show that there is a significant relationship between use of gadget and students' learning achievement with a correlation coefficient of 0,493 which is included in the medium category. So it can be concluded that there is a positive and significant relationship between the use of gadget and the learning achievement of high grade students of SD Inpres 7/83 Manurunge Ulaweng District Bone Regency. Keywords: Use of Gadgets. Learning Achievement